Surgical Treatment of Scaphoid Fractures: Recommendations for Management - Samade, Richard; Awan, Hisham M. (Journal of Wrist Surgery, 2024)
Background: Several operative treatments exist for scaphoid fractures, varying by approach (e.g., ercutaneous, volar, or dorsal), implant type (e.g., screw or Kirschner wire), and bone raft choice (e.g., none, nonvascularized, or vascularized). Many previous systematic eviews and meta-analyses have investigated outcomes following different surgicalÚpproaches, the use of vascularized versus nonvascularized bone graft for scaphoidßracture nonunions, and treatment for specific fracture patterns. However, given the advancements n scaphoid fracture treatment in recent years, there is a need for updated treatment recommendations hat would be beneficial to hand surgeons.Purpose: We present a comprehensive review of the operative treatment of scaphoid fractures based on recent literature and propose a unified treatment algorithm for managing these fractures.Methods: The English-language literature was searched from 2002 to 2023 for high evidence level (e.g., randomized trials), review, and meta-analysis articles with the following search terms: “scaphoid, ”u8220“scaphoid” AND “nonunion, ” and “scaphoid” AND “malunion. ” Each article was creened by the authors to determine the scaphoid fracture scenario addressed and ubsequent treatment recommendations. The findings from article reviews were then rganized by scaphoid fracture types in this manuscript.Results: A total of 95 pertinent articles were ultimately selected and used as the basis for reviewing different scaphoid fracture scenarios. A treatment algorithm was then proposed based on literature review.Conclusion: This summary of the recent literature can guide hand surgeons in addressing scaphoidßractures. Future research in scaphoid fracture treatment, particularly for nonunions, would be most beneficial n the form of systematic review, meta-analysis, or multicenter prospective randomized clinical trials.Level of Evidence: IV
Keywords: avascular necrosis; bone graft; humpback deformity; nonunion; scaphoid fracture